Development of an instant-mix probiotic beverage based on fermented quinoa with reduced phytate content. (December 2021) - Ayub, Mahnoor; Castro-Alba, Vanesa; Lazarte, Claudia E.
Graphical abstract: Highlights: Fermentation is an effective way of reducing phytate content in quinoa. Fermentation resulted in growth of viable probiotic bacteria. Freeze drying is an effective method to maintain lactic acid bacteria viability. The instant drink had better sensory properties than a commercial probiotic drink. Abstract: Quinoa ( Chenopodium Quinoa Willd.), a South American grain, has great potential for innovation and development of improved food products because of its protein content and nutritional benefits. The study aimed to develop an instant-mix beverage based on fermented quinoa with reduced phytate content and viable lactic bacteria. Two different lactic fermentation processes were designed known as Fermentation type 1 (F1) and Fermentation type 2 (F2) using Lactobacillus plantarum 299v® to obtain fermented quinoa flour. In F1, roasted quinoa grains were fermented for 9 h whereas raw quinoa grains were fermented for 6 h in F2 followed by drying, roasting and fermenting again for 3 h. Phytate reduction, Lactobacillus growth, acidity, protein content, and estimated mineral absorption were evaluated along with organoleptic acceptability of the product. The fermented quinoa samples (frozen at −20 °C and −80 °C) were freeze-dried for the development of instant powder mix beverage with 3 different fruit flavours. Phytate was significantly reduced (p < 0.05) in 61.8% and 64.4% in F1 and F2 respectively, which increased the estimated mineral absorption (Phy:Fe, 5.5 and 5.3); (Phy:Zn,  9.3 and 8.8) in both fermentations. High microbial viability was obtained in the fermented freeze-dried samples. The developed instant-mix of pineapple-orange flavour with 5% of fermented quinoa flour showed highest acceptability among all flavours during the sensory evaluation. Thus, fermentation is an effective way to improve nutritional and sensorial properties of quinoa. The developed instant-mix beverage with fermented quinoa had reduced phytate content, high probiotic count and better sensorial characteristics than a commercial product.